Physiological effects of a companion robot on blood pressure of older people in residential care facility: A pilot study. (25th December 2013) - Robinson, Hayley; MacDonald, Bruce; Broadbent, Elizabeth
<x xml:space="preserve">Abstract</x> Aim To investigate the effects of interacting with the companion robot, Paro, on blood pressure and heart rate of older people in a residential care facility. Methods This study used a repeated measures design. Twenty‐one residents in rest home and hospital level care had their blood pressure taken three times; before, during and after interacting with the seal robot. Results Four residents who did not interact with the robot were excluded from the final analysis (final n = 17). The final analysis found that systolic and diastolic blood pressure changed significantly over time as did heart rate. Planned comparisons revealed that systolic and diastolic blood pressure decreased significantly from baseline to when residents had Paro (systolic, P = 0.048; diastolic, P = 0.05). Diastolic blood pressure increased significantly after Paro was withdrawn (P = 0.03). Conclusion Interacting with Paro has a physiological effect on cardiovascular measures, which is similar to findings with live animals.